Oral Health Status and Treatment Needs of Visual Impairment in Phitsanuloke, Thailand - Samnieng, Patcharaphol; Seehaumpai, Pakinai; Wichachai, Supattra; Yusookh, Patcharawan (Journal of Dentistry Indonesia, 2014)
There is little information on the oral health status of visual impairment in Thailand. Objective: To investigate the oral health status and dental treatment needs of visual impaired Thai. Method: The subjects were 146 visual impairment (70 males and 76 females, mean age 48.8 ± 5.9), who live in Phitsanuloke, Thailand. Information on self-perceived oral health problems, oral function and oral health behavior was obtained via questionnaires. Oral examinations investigated the Decay Missing Filling Teeth (DMFT), Simplified Oral Hygiene Index (OHIS) and prosthetic needs index. Results: The mean DMFT score was 16.0 (DT=4.4, MT=10.2, FT=1.4), the mean number of teeth present was 15.5. 35% of subjects needed dental fillings and 12.3% required tooth extractions. 34.8% had periodontal disease and mean OHIS score were 2.52. Thirty-eight percent of subjects need both upper and lower partial dentures. Visual impaired suffer from oral function problems (speaking problem 26.5%, swallowing problem 32.6%, tasting problem 29.2% and chewing problem 45.2%). Conclusion: The oral health status of visual impairment was poor due to high levels of tooth loss, caries experience and periodontal disease. Therefore, it is important to have a proper preventive approach and service delivery programs to improve the oral health condition of this population.